Southeast Asian tribes, minorities and nations. - Kunstadter, Peter (Princeton Legacy Library, 2017)
A major source of political instability in Southeast Asia has been ethnic diversity and the lack of congruence between ethnic distributions and national boundaries. Here twenty specialists base their papers largely on original field work in Burma, China, India, Laos, Malaysia, Thailand, and Vietnam. Contrary to the usual picture of tribal people as isolated, homogeneous, stable, and conservative, the papers show tribesmen are often a dynamic force in the modern history of Southeast Asian states. Descriptions of tribal life and government programs, together with charts, tables, maps, and photographs give a wealth of data. Originally published in 1967. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.